(untitled) (Development Service Industry Management, 2024)
The article examines the concept of a quantum leap in the economy of the 20th century; historical and theoretical aspect, practical nature of the development of quantum innovation. To achieve this goal, the theoretical justification of quantum leaps in the economy of the 20th century was analyzed; researched how radical innovations and quantum technologies influence the global processes of economic development, change the market structure and create new models of management and business development. Ideas of innovative theory based on the main mechanisms of economic development are considered and the role of economic transformations is highlighted; the concept of "great innovation cycles", which reflects the cyclical nature of technological change with an impact on the economy and development. The article considers a quantum algorithm that improves the accuracy of forecasting market trends, and organizations effectively plan the development of innovations, forecast consumer demand, and analyze competitiveness. It was determined that the implementation of quantum technologies improves innovation potential and economic growth in the face of limitations and risks, which include: • Large-scale investments. Quantum technologies involve increased initial development and implementation costs. Organizations face investment challenges in the early stages of quantum technology development. • Lack of professional personnel. Quantum technologies require professionally trained specialists in quantum physics, electronics, economics, and quantum engineering. The lack of professional personnel hinders the implementation of quantum technology and complicates market implementation. • Information security risks. Quantum cryptography, despite its advantages, breaks modern cryptographic systems and creates information security risks. Companies master information protection techniques and adapt security systems to new threats. • Unpredictability of the legal system. Quantum technology is implemented against the backdrop of legal uncertainty, because current standards and regulations do not take into account the specific features of quantum technology. New standards and regulations aimed at stimulating the introduction of quantum technologies into the economy are being mastered by state bodies. The results of the study are recommended for further scientific developments in the application of quantum technology. The conclusion is the use of quants, which leads to a change in the structure of the world economy, the concentration of economic power to the movement of competitive enterprises. The conclusion proposes to develop concerted actions of the government, business community and scientists in the field of quantum physics research, funding of scientific programs, stimulation of cooperation between academies and universities with business. The integration of knowledge in physics, mathematics, informatics and economics explains the impact of quantum dynamics on the innovation process and macroeconomic trends.